2013
DOI: 10.1155/2013/517570
|View full text |Cite
|
Sign up to set email alerts
|

NovelGUCA1AMutations Suggesting Possible Mechanisms of Pathogenesis in Cone, Cone-Rod, and Macular Dystrophy Patients

Abstract: Here, we report two novel GUCA1A (the gene for guanylate cyclase activating protein 1) mutations identified in unrelated Spanish families affected by autosomal dominant retinal degeneration (adRD) with cone and rod involvement. All patients from a three-generation adRD pedigree underwent detailed ophthalmic evaluation. Total genome scan using single-nucleotide polymorphisms and then the linkage analysis were undertaken on the pedigree. Haplotype analysis revealed a 55.37 Mb genomic interval cosegregating with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…The CD and CRDs display genetic and phenotypic heterogeneity rendering genetic diagnosis challenging. Colobomalike macular atrophy is a rare phenotypic association in CD and CRD, with variants identified in ADAM9 and GUCA1A in only a few cases [14,15]. Other IRDs associated with coloboma-like macular atrophy include North Carolina Macular dystrophy, early-onset retinitis pigmentosa and LCA [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The CD and CRDs display genetic and phenotypic heterogeneity rendering genetic diagnosis challenging. Colobomalike macular atrophy is a rare phenotypic association in CD and CRD, with variants identified in ADAM9 and GUCA1A in only a few cases [14,15]. Other IRDs associated with coloboma-like macular atrophy include North Carolina Macular dystrophy, early-onset retinitis pigmentosa and LCA [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Another peculiar feature of the apo state was a conserved pair of H-bonds between the backbone groups NH of Ile 107 and C_O of Leu 151 and NH of Leu 153 and C_O of Gly 105, which created a short antiparallel β-sheet stable during the 200 ns simulation, which contributed to maintain EF3 and EF4 in an open conformation. Interestingly, both residues Ile 107 and Leu 151 have been found to be mutated respectively in Thr and Phe in patients suffering from cone dystrophy [47,48]. Another similarly short β-sheet was observed between EF1 and EF2, which however was not stable during the production phase.…”
Section: Structural Dynamics Of Putative Gc-activating States Over 20mentioning
confidence: 99%
“…Mutations in GUCA1A, encoding for GCAP1 result in aberrant GC regulation and in retinal degeneration, a set of progressive diseases involving cones, the macula, and in some cases rods, ultimately leading to blindness [11][12][13]. To date, 20 GCAP1 variants have been associated with retinal dystrophy [14][15][16][17][18][19][20][21][22][23][24][25], with one of the most recently discovered being the G86R mutation, located in the previously mentioned hinge region [26]. Biochemical experiments performed with the GC-GCAP1 reconstituted system in the presence of the G86R mutation showed that the complex forms with higher affinity than the WT and it is unable to decelerate the GC at high Ca 2+ -levels corresponding to the dark-adapted state [26].…”
Section: Introductionmentioning
confidence: 99%